Penyelesaian Sengketa Akibat Perjanjian Nominee Melalui Kesepakatan Perdamaian - Cokorda Istri Agung Mahayuni; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
The provisions of the UUPA state that only Indonesian citizens (WNI) can own property rights over land. In order to overcome this, nominee agreements are made to control the ownership rights of the land. This practice often leads to disputes between Indonesian citizens and foreigners that reach the courts. Land ownership by foreigners with the status of right of use is based on Government Regulation No. 103 Year 2015. The arrangements for resolving nominee agreement disputes through mediation are Law Number 30 of 1999, PERMA Number 1 of 2016, BPN Decree Number 34 of 2007, and Technical Guidelines Number: 05/JUKNIS/D.V/2007. The formulation of the problem is: 1) "How is the regulation of nominee agreement dispute resolution through a pre-decree agreement? "And 2) How is the mechanism for resolving land rights nominee agreement disputes through mediation?" The research method used is normative law with a statutory and conceptual approach. The results obtained by the Government are to pay attention to laws and regulations that regulate explicitly and specifically regarding nominee agreements in Indonesia.